Necrotizing Fasciitis‐Induced Septic Shock due to Aeromonas hydrophila: A Case Report - Gongjie Ye; Taohong Li; Yiru Weng; Zhouzhou Dong (Clinical Case Reports)
ABSTRACT Aeromonas hydrophila (A. hydrophila), a Gram‐negative bacterium commonly found in aquatic environments, has the capacity to be transmitted to humans through consumption of contaminated fish, water, or seafood. In this study, we present a case report concerning a 77‐year‐old female patient who experienced an acute exacerbation of chronic heart failure, subsequently developing severe septic shock due to necrotizing fasciitis caused by A. hydrophila. Infections caused by A. hydrophila are more prevalent during warmer months, particularly in regions characterized by dense aquaculture or the presence of natural water bodies. The excessive use of antibiotics in aquaculture has contributed to the emergence of antibiotic‐resistant A. hydrophila strains. The proliferation of multidrug‐resistant A. hydrophila presents a significant challenge for clinicians. In the context of atypical bacterial infections, the initial empiric therapy typically involves the use of third‐generation cephalosporins in conjunction with quinolone antibiotics. In the present case, the patient's successful recovery was achieved through the administration of a combination of cefoperazone/sulbactam and levofloxacin, as determined by sensitivity testing. This case study underscores the critical importance of considering A. hydrophila infection in patients with septic shock who present with necrotizing fasciitis.